EVALUATION OF SOME ADVANCED MID-SEASON POTATO HYBRIDS FOR NORTH-EAST ALLUVIAL PLAINS OF BIHAR - Yadav, L. M.; Jha, G.; Roy, R.; Singh, S. P. (Potato Journal, 2013)
A field experiment was conducted during the year 2003-2004 in two sets harvested at 60 days and 75 days respectively at Dholi farm situated in the agro climatic Zone I of Bihar to evaluate seven hybrids viz., J/92-167, J/ 93-4, J/93-77, J/93-81 J/93-86, J/93-87 and J/93-139 against two controls Kufri Ashoka and Kufri Jawahar. The experiment was planted in RBD with three replications on 19-11-03 in plot size of 3m x 2.4 m with spacing of 60cm x 20 cm. The data on percent plant emergence at 30 days, total and marketable tuber yield (>20g) at 60 days and 75 days after sowing and percent tuber dry matter of the hybrids/verities under investigations were recorded. Plant protection measures were taken as per recommendation. The data showed no significant differences among the hybrids/verities for percent plant emergence at 30 DAS in both the sets of experiments, but hybrid J/93/-81 having 81.73 and 89.27 percent plant emergence proved superior. The variation in total and marketable tuber yield were non significant at 60 DAS, whereas hybrids/verities showed significant differences in 75 days crop. The hybrid J/93-81 proved highest yielder with 252.78 and 236.11q ha-1 for total and marketable tuber yield respectively and was found significantly superior to variety Kufri Ashoka for both parameters. The hybrids/verities showed significant differences for percent tuber dry matter in both the sets of experimentation and hybrid J/93-139 and cv. Kufri Jawahar had higher percent tuber dry matter (16.26 and 17.13 percent, respectively). Keeping in view all the parameters under study, the overall performance of hybrid J/93-81 proved its superiority over all the hybrids/verities and found suitable for Zone-I of Bihar.